The role of students' age, problem type and situational context in solving mathematical word problems - Vlahović-Štetić, Vesna (Array, 2004)
The aim of this research is to test the hypotheses regarding the importance of understanding situation in mathematical word problems that follow from Reusser's Situation Problem Solver (SPS) model by exploring efficiency in children's mathematical word problems solving as a function of age, problem type and situational context of the problem. Children of three age groups participated in the study: preschool kindergarten group (N=67), first grade (N=79) and second grade students (N=85). Testing was conducted by 20 specially trained senior psychology students. Two categories of word problems were used: change problems and compare problems. Every child was tested twice, one time with neutral context problems, and the other time with familiar context problems. Repeated measures analysis of variance was performed with age, situational context and problem type as independent variables and children's performance as a dependent variable. All main effects were significant, as well as the interaction of age and problem type. The results indicate that older children are more successful than younger children in solving mathematical word problems and that the children's performance on the change problems is better than on compare problems. Results also showed that children's performance on the problems with familiar context was better than performance on the problems with neutral context. In both problem types performance of school children was better than performance of kindergarten children. These results confirm Reusser's essential hypothesis that including additional sense to the problem text would facilitate designing the situational model of the problem.